The PPP-Family Protein Phosphatases PrpA and PrpB of Salmonella enterica Serovar Typhimurium Possess Distinct Biochemical Properties - Shi, Liang (American Society for Microbiology, 2001)
Salmonella enterica serovar Typhimurium requires Mn(2+), but only a few Mn(2+)-dependent enzymes have been identified from bacteria. To characterize Mn(2+)-dependent enzymes from serovar Typhimurium, two putative PPP-family protein phosphatase genes were cloned from serovar Typhimurium and named prpA and prpB. Their DNA-derived amino acid sequences showed 61% identity to the corresponding Escherichia coli proteins and 41% identity to each other. Each phosphatase was expressed in E. coli and purified to near electrophoretic homogeneity. Both PrpA and PrpB absolutely required a divalent metal for activity. As with other phosphatases of this class, Mn(2+) had the highest affinity and stimulated the greatest activity. The apparent K(a) of PrpA for Mn(2+) of 65 μM was comparable to that for other bacterial phosphatases, but PrpB had a much higher affinity for Mn(2+) (1.3 μM). The pH optima were pH 6.5 for PrpA and pH 8 for PrpB, while the optimal temperatures were 45 to 55°C for PrpA and 30 to 37°C for PrpB. Each phosphatase could hydrolyze phosphorylated serine, threonine, or tyrosine residues, but their relative specific activities varied with the specific substrate tested. These differences suggest that each phosphatase is used by serovar Typhimurium under different growth or environmental conditions such as temperature or acidity.